Consequences of Sanctions on the Aggravation of the Effects of Climate Change - Mehrdad Moghadam khorsand; Maryam RazehKeisami (Nīvār)
Climate change is one of the most important challenges facing humanity in the 21st century. This phenomenon is caused by the increase of greenhouse gases in the earth's atmosphere, which causes the warming of the earth, the melting of ice, the rise of the sea level, the occurrence of extreme weather phenomena and other environmental and social consequences. Sanctions are also one of the powerful foreign policy tools that can have wide-ranging effects on the economy and politics of the target society. Sanctions can reduce countries' incomes, increase import costs, reduce exports, disrupt supply chains, and lead to other economic problems. Governments should think of the necessary arrangements and measures such as creating compensation mechanisms, increasing international cooperation, developing domestic capacities, localizing the required equipment and tools, supporting domestic production and successful and stylish producers, and providing the necessary incentives to elites and owners. thinking, increasing the export of goods and services, creating convergence with other aligned governments, caution in the consumption of natural resources, diversification in energy consption and replacing renewable energies with fossil fuels and other practical and executive measures to reduce the consequences of sanctions and the effects of climate change to cope effectively.